2021
DOI: 10.3389/fcvm.2021.715842
|View full text |Cite|
|
Sign up to set email alerts
|

γ' Fibrinogen as a Predictor of Survival in Amyotrophic Lateral Sclerosis

Abstract: Amyotrophic lateral sclerosis (ALS) is an aggressive neurodegenerative disorder related to neuroinflammation that is associated with increased risk of thrombosis. We aimed to evaluate γ' fibrinogen plasma level (an in vivo variant of fibrinogen) as a biomarker in ALS, and to test its role as a predictor of disease progression and survival. Sixty-seven consecutive patients with ALS were followed and the results were compared with those from 82 healthy blood donors. Patients were clinically evaluated at the time… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 20 publications
(35 reference statements)
1
4
0
Order By: Relevance
“…No other independent variable showed significant association with survival. The average survival in our ALS population was similar to other ALS studies 48,49 …”
Section: Resultssupporting
confidence: 89%
“…No other independent variable showed significant association with survival. The average survival in our ALS population was similar to other ALS studies 48,49 …”
Section: Resultssupporting
confidence: 89%
“…Other studies have shown a positive correlation between the concentration of FIBB and survival in ALS patients [ 39 ]. Specifically, ALS patients who had higher levels of FIBB in their plasma exhibited longer survival periods, a finding consistent across various potential influencing factors like age, gender, respiratory issues, or functional ability [ 40 ]. C9 is among the proteins engaged in the complement system, serving as a defense mechanism of the body against pathogens [ 41 ].…”
Section: Discussionmentioning
confidence: 88%
“…Studies have reported thinner fibers and a more branched network in clots made with γA/γ' fibrinogen compared to clots prepared from γA/γA fibrinogen [19][20][21] . γ' fibrinogen levels can vary largely between individuals and are associated with various diseases [22][23][24][25][26][27] .…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…[19][20][21] γˊfibrinogen levels can vary largely between individuals and are associated with various diseases. [22][23][24][25][26][27] Since fibrinogen variants were previously associated with various thrombotic diseases and an altered fibrin network structure, we hypothesized that these fibrinogen variants would be increased in patients with severe COVID-19 and thrombosis. Therefore, we investigated whether levels of functional fibrinogen, total fibrinogen, intact fibrinogen, γf brinogen, and α E fibrinogen are altered in COVID-19 and whether this can explain why some patients with COVID-19 develop thrombosis and others do not.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation